Methods for identification of causative agents of dangerous and particularly dangerous infections based on the analysis of nucleic acids - Y. A. Kibirev; S. E. Burlachuk; A. S. Grudcina; D. O. Sityakov; S. G. Isupov; V. I. Drobkov (Вестник войск РХБ защиты)
One of the main tasks of the NBC Protection Troops is accurate and rapid identification of infectious disease causative agents in case of establishing the fact of biological contamination. Different methods based on the analysis of nucleic acids are most preferred for this purpose. Most of them are based on DNA amplification by polymerase chain reaction (PCR). The result is detected by electrophoretic separation of amplification products, as well as by registration of endpoint fluorescent signal (FLASH modification) or in real time (PCR-RT). Other methods of DNA amplification, such as ligase chain reaction (LCR) and isothermal amplification, are also applicable in practice. The article also describes some identification methods based on nucleic acid sequencing: multilocus sequence typing (MLST) method, sequencing of individual genes and complete genome sequencing. It is concluded that the choice of identification method should be based on the goals and objectives, laboratory facilities, availability of trained personnel and funding levels. Despite the fact that the most informative are methods based on sequencing nucleotide sequences, their implementation in the field is difficult so far due to technological requirements.